Discrepant Drinking and Partner Violence Perpetration Over Time in Lesbians' Relationships. (August 2018) - Lewis, Robin J.; Winstead, Barbara A.; Braitman, Abby L.; Hitson, Phoebe
Discrepant drinking (i.e., differences in alcohol use) and perpetration of intimate partner violence in same-sex female couples were examined. Self-identified lesbian participants were recruited from market research firms and reported on their own and their partner's alcohol use and their own perpetration of psychological aggression and physical violence at baseline, then 6 and 12 months later. Cross-lagged panel analyses revealed that discrepant drinking predicted participants' subsequent perpetration of psychological aggression but not physical violence. Both psychological aggression and physical aggression predicted subsequent discrepant drinking. Consistent with findings in heterosexual couples, differences in alcohol use appear to be a risk factor for relationship aggression.